Rencana Induk Pembangunan Kepariwisataan Daerah Denpasar dan Yogyakarta: Studi Komparasi dan Pembelajaran - Marius Yosef Seran; Putu Guntur Pramana Putra; I Nengah Sandi Artha Putra; Laurensius Sandrio; Yosef Kurniawan Ukar (Pusat Penelitian dan Pengabdian Politeknik eLBajo Commodus, 2024)
The Denpasar Tourism Development Master Plan Regional Regulation for 2018-2029 No. 3 of 2019 and The Yogyakarta Tourism Development Master Plan Regulation for 2015-2025 No. 3 of 2015 serve as guiding documents for the future trajectory of tourism development in their respective regions over the next decade. These regulations are instrumental in ensuring that the progression of tourism aligns with predetermined visions and objectives. This study adopts a comparative approach, which involves analyzing and contrasting the two regulations to draw insights. Comparative analysis is employed as a method to scrutinize data and derive new insights. The findings from this analysis reveal both similarities and disparities between the two regulations. Commonalities include shared objectives, legal underpinnings such as UU 1945 article 18, paragraph 6, adherence to Law no. 10 of 2009, regulatory types, timeframes, and general provisions. However, distinctions emerge in discussions about general and specific differences. Regarding tourism development objectives outlined in each regulation, such as those Denpasar Regional Regulation No. 3 of 2019, article 13 and Yogyakarta Regional Regulations No. 3 of 2015, article 7, both emphasize similar goals: fostering the growth of the creative economy, enhancing employment opportunities, boosting regional income, and safeguarding the environment. The effective implementation of these regulations of expected to yield positive outcomes for all stakeholders involved in tourism development.